Cracked tooth syndrome and strategies for restoring - KORKUT, BORA; TAĞTEKİN, DİLEK (My University, 2023)
Purpose of Review The restorative management of cracked tooth syndrome (CTS) is very complex and depends on the prerestorative diagnosis and decisions. This review discusses the strategies for restoring teeth with CTS and suggests a related clinical decision tree. Recent Findings CTS is the incomplete fracture of the natural tooth crown. Preparation type and direct/indirect restorative protocol choices are the important factors efecting the prognosis of the tooth while multi-factorial etiology, complexity in diagnosis, and subjective decisions about the preparation make the clinical management very difcult. Therefore, the clinical management of CTS should be carried out by the guidance of an informative decision tree. This decision tree should focus on (1) the rational retention of tooth structure, (2) the preparation optimization, and (3) the restorative implications and choices. Summary The restorative management of CTS is a complex issue which should be carried out systematically. The guidance of an informative, universal decision tree might be useful in daily clinical practice.
Keywords: Crack; Fracture; Cracked tooth syndrome; Restoration